1990
DOI: 10.1007/bf01868675
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the macromolecular barrier at cell extrusion sites in intestinal epithelium: Physiological rearrangement of tight junctions

Abstract: All epithelia slough dying cells but the consequences of this physiological process to epithelial barrier function is unknown. In mammalian small intestine absorptive cells are known to migrate from the villus base to the villus tip from which they slough. These villus tip extrusion zones are often envisioned as sites at which macromolecules could leak across the epithelium. However, only trace amounts of macromolecules cross this epithelium even though, based on known epithelial turnover rates, extrusion even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
166
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 11 publications
11
166
5
Order By: Relevance
“…Apoptosis is a regulated process of cell death, and single epithelial cell apoptosis and extrusion without loss of barrier function are normal physiological events in the gastrointestinal tract (Madara, 1990;Abreu et al, 2000), but an increased epithelial apoptotic ratio might be another cause of relevant leaks in the epithelial barrier (Gitter et al, 2000). The present study demonstrated that epithelial apoptosis in all intestinal segments was considerably up-regulated in the challenged birds compared with the unchallenged birds, which suggested that C. perfringens challenge may disrupt epithelial barrier function by apoptosis-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a regulated process of cell death, and single epithelial cell apoptosis and extrusion without loss of barrier function are normal physiological events in the gastrointestinal tract (Madara, 1990;Abreu et al, 2000), but an increased epithelial apoptotic ratio might be another cause of relevant leaks in the epithelial barrier (Gitter et al, 2000). The present study demonstrated that epithelial apoptosis in all intestinal segments was considerably up-regulated in the challenged birds compared with the unchallenged birds, which suggested that C. perfringens challenge may disrupt epithelial barrier function by apoptosis-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…By freeze-fracture and light and electron microscopic studies, effete enterocytes at the villus tips of rat and hamster small intestine have been shown to extrude into the lumen, during which juctional complexes of extruding enterocytes with neighboring cells are maintained by proliferating juctional elements along the lateral margin of the cells (MADARA, 1990). As mentioned above, the apical cytoplasmic pieces at the villus tips of the guinea pig small intestine maintain junctional complexes with adjacent enterocytes, while the adjacent enterocytes form new junctional complexes beneath the exfoliating apical cytoplasmic pieces when they are exfoliated from the villus tips (IWANAGA et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that macrophages in the lamina propria of the human small intestine do not participate in the exfoliating process of effete enterocytes. This notion is compatible with the present findings that the outward blebbing of effete enterocytes and apoptotic bodies were not detected at the villus tips, supporting the hypothesis that the shrinkage of effete enterocytes is mediated by inward blebbing, reflecting the presence of numerous clear vesicles in the cells.By freeze-fracture and light and electron microscopic studies, effete enterocytes at the villus tips of rat and hamster small intestine have been shown to extrude into the lumen, during which juctional complexes of extruding enterocytes with neighboring cells are maintained by proliferating juctional elements along the lateral margin of the cells (MADARA, 1990). As mentioned above, the apical cytoplasmic pieces at the villus tips of the guinea pig small intestine maintain junctional complexes with adjacent enterocytes, while the adjacent enterocytes form new junctional complexes beneath the exfoliating apical cytoplasmic pieces when they are exfoliated from the villus tips (IWANAGA et al, 1993).…”
mentioning
confidence: 99%
“…A recently published study by Madara (1990) proposes that intestinal epithelial junctional complexes undergo dynamic changes when an exfoliating cell reaches the site of extrusion. Junctional complexes must be maintained to maintain the epithelial barrier, so complexes in adjacent migrating cells must also act in a similar dynamic fashion.…”
Section: Discussionmentioning
confidence: 99%